2021
DOI: 10.1136/lupus-2021-000523
|View full text |Cite
|
Sign up to set email alerts
|

ANA-positive primary immune thrombocytopaenia: a different clinical entity with increased risk of connective tissue diseases

Abstract: ObjectivePrimary immune thrombocytopaenia (ITP) is highly heterogeneous. ANA-positive primary ITP may resemble the preclinical stage of connective tissue diseases (CTDs), but is still considered primary ITP due to a controversial CTD risk assessment in this group. The objective of this study was to clarify the risk of CTD in ANA-positive patients with primary ITP.MethodsWe performed a retrospective cohort study and a meta-analysis. 586 patients with newly diagnosed primary ITP were followed up and Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
(36 reference statements)
2
17
0
Order By: Relevance
“…To date, no other study on primary ITP has reported an association between ANA titres and platelet counts in the paediatric population. An adult primary ITP cohort was studied using an ANA titre of 1:100 as a threshold for positive ANA, and found lower platelet counts at diagnosis in ANA‐positive patients compared to ANA‐negative patients (median value, 34 × 10 9 /l vs 46 × 10 9 /l, p value 0.015), which is consistent with our findings 12 . Furthermore, the results of our study showed that although children with higher ANA titres had lower platelet counts at the beginning, a subsequent more rapid rise in platelet counts was found, suggesting that high‐titre ANA did not result in a worse outcome of subsequent platelet counts in children with primary ITP.…”
Section: Discussionsupporting
confidence: 90%
“…To date, no other study on primary ITP has reported an association between ANA titres and platelet counts in the paediatric population. An adult primary ITP cohort was studied using an ANA titre of 1:100 as a threshold for positive ANA, and found lower platelet counts at diagnosis in ANA‐positive patients compared to ANA‐negative patients (median value, 34 × 10 9 /l vs 46 × 10 9 /l, p value 0.015), which is consistent with our findings 12 . Furthermore, the results of our study showed that although children with higher ANA titres had lower platelet counts at the beginning, a subsequent more rapid rise in platelet counts was found, suggesting that high‐titre ANA did not result in a worse outcome of subsequent platelet counts in children with primary ITP.…”
Section: Discussionsupporting
confidence: 90%
“…81 Consistent with these findings, Liu et al, in a historical cohort study and in a meta-analysis, confirmed that ANA-positive primary ITP is a distinct subgroup of primary ITP associated with an increased risk of developing a CTD, especially SLE as compared with the ANA-negative ITP group. 82 In this study, ANA-positive primary ITP patients had a 48-fold higher risk of newonset SLE than ANA-negative ITP patients, suggesting that ANA positivity confers a high risk of developing lupus. 82 Of note, the highest risk of developing CTD was during the first 4 years after ITP diagnosis, and low C3 levels and positive anti-Ro antibodies were more frequently found in those who developed a CTD.…”
Section: Immune Thrombocytopenic Purpuramentioning
confidence: 52%
“…82 In this study, ANA-positive primary ITP patients had a 48-fold higher risk of newonset SLE than ANA-negative ITP patients, suggesting that ANA positivity confers a high risk of developing lupus. 82 Of note, the highest risk of developing CTD was during the first 4 years after ITP diagnosis, and low C3 levels and positive anti-Ro antibodies were more frequently found in those who developed a CTD. 81 In view of these findings, some authors recommend that patients with ITP, particularly those who are ANA positive, should be closely monitored for SLE, especially within the first 5 years of diagnosis, and preferably be evaluated by a rheumatologist to identify nonhematological manifestations suggestive of SLE.…”
Section: Immune Thrombocytopenic Purpuramentioning
confidence: 52%
See 1 more Smart Citation
“…For the same reason, it is difficult to get evidence whether the presence of ANA results in a higher risk of developing systemic lupus in patients with primary ITP. 30 In a recently published retrospective Chinese study, 10 of 130 adult patients with primary ITP (7.7%) with a mean follow-up of 6 years developed systemic lupus. The median time from ITP diagnosis to systemic lupus onset was 2.5 years.…”
Section: Risk Of Systemic Lupusmentioning
confidence: 99%